Bioactivity of Biosilica Obtained From North Atlantic Deep-Sea Sponges - Dudik, Olesia; Amorim, Sara; Xavier, Joana R.; Rapp, Hans Tore; Silva, Tiago H.; Pires, Ricardo A.; Reis, Rui L. (Frontiers in Marine Science, 2021)
Demosponges are a well-known source of a plethora of bioactive compounds. In particular, they are able to form a skeleton by direct deposition of silica in a process catalysed by silicatein. Herein, we isolated biosilicas from five different Atlantic deep-sea sponges Geodia atlantica (GA), Geodia barretti (GB), Stelletta normani (SN), Axinella infundibuliformis (AI) and Phakellia ventilabrum (PV) to explore the bioactivity and osteogenic capacity of its silica-based materials. We chemically characterized the isolated biosilicas and evaluated them for their bioactivity to deposit Ca and P on their surface (by immersion in simulated body fluid, SBF). GB-, SN-, AI- and PV-based biosilicas did not generate a stable calcium phosphate (CaP) layer over time in the presence of SBF, however, the GA-derived one was able to form a CaP surface layer (at a Ca/P ratio of 1.7, similar to the one observed for hydroxyapatite), that was stable during the 28 days of testing. In addition, no cytotoxicity towards L929 and SaOs2 cells was observed for the GA-based biosilica up to a concentration of 10 mg/mL. Overall, the GA-based biosilica presents the characteristics to be used in the development of biomaterials for bone tissue engineering.